WOMEN'S ECONOMIC RIGHTS IN THE QUR'AN QURAISH SHIHAB'S PERSPECTIVE IN TAFSIR AL-MISBAH - Syifaul Alami; Fatihunnada F.; Hasan Basri Salim; Nanang Lidwan; Mutawakkil Faqih; Sudiyo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
In the study of Islamic exegesis, the issue of gender equality—particularly regarding women's economic rights—often receives insufficient attention. Most traditional interpretations tend to uphold patriarchal views that limit women's roles in the economic sphere. Using a library research method, this study finds that Quraish Shihab's approach differs from traditional interpretations, which tend to be literal and ignore the socio-cultural context of the time. Through his moderate and contextual approach, Quraish Shihab allows for a reinterpretation of Qur'anic verses so they remain relevant to contemporary developments. This enables the application of just and inclusive Islamic values ​​across various aspects of life, including in the economic domain. His interpretation does not advocate for absolute equality but rather aligns rights and responsibilities according to individual capacities, making it more relevant to modern social dynamics. The findings show that Islam provides space for women to participate in economic activities, own property, work, and manage assets independently, while upholding the principle of justice rather than absolute equality. Therefore, women's economic rights must be recognized and protected in accordance with their capacities and responsibilities.